2000
DOI: 10.1007/s001340000758
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of spontaneous breathing: potential marker for weaning outcome

Abstract: The spontaneous breathing pattern during minimal mechanical ventilatory support is more chaotic in patients who failed extubation trials compared to patients who passed extubation trials. Thus, we speculate that characterizing the SB pattern during minimal ventilatory support might be a useful tool in differentiating between extubation success and failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…In 2001, El-Khatib et al . showed that during the SBT, 13 patients who failed extubation (defined as reintubation within 24 hours) had lower complexity than 39 patients who were successfully extubated [36]. In 2003 Shen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, El-Khatib et al . showed that during the SBT, 13 patients who failed extubation (defined as reintubation within 24 hours) had lower complexity than 39 patients who were successfully extubated [36]. In 2003 Shen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The different results from Engoren's and El-Khatib studies [72,75] were attributed to the prevailing conditions during respiratory variability analysis. According to Caminal and Brochard, different levels of pressure support may alter breath-to-breath variability in an inverse way [79,80], something that could have played a role in the two previous studies.…”
Section: Breathing Variability and Complexity Indices As Weaning Predmentioning
confidence: 88%
“…El-Khatib et al [75] studied 52 patients diagnosed mostly with lung diseases and under mechanical ventilation in two phases: 1. under synchronized intermittent mandatory ventilation (SIMV) with RR ≤ 4 breaths/min and with no PS for 60 minutes and 2. during a CPAP trial of 5 cm H2O with no PS ventilation for other 60 minutes. Thirty-nine patients (75%) were successfully extubated and the remaining 13 patients failed weaning trial.…”
Section: Breathing Variability and Complexity Indices As Weaning Predmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite optimizing these components, extubation failure still occurs in 2 to 25% of cases in the intensive care unit (ICU) likely from a disparity between work of breathing (WOB) and capacity of respiratory muscles [1, 2]. A trial of spontaneous breathing (SBT) is typically performed prior to extubation as a predictor of success [1, 3]. If a patient breathes shallow and rapidly during the trial, the patient may not tolerate spontaneous breathing [1, 3].…”
Section: Introductionmentioning
confidence: 99%